If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-6(6x-2)=-6(5x+5)
We move all terms to the left:
-6(6x-2)-(-6(5x+5))=0
We multiply parentheses
-36x-(-6(5x+5))+12=0
We calculate terms in parentheses: -(-6(5x+5)), so:We get rid of parentheses
-6(5x+5)
We multiply parentheses
-30x-30
Back to the equation:
-(-30x-30)
-36x+30x+30+12=0
We add all the numbers together, and all the variables
-6x+42=0
We move all terms containing x to the left, all other terms to the right
-6x=-42
x=-42/-6
x=+7
| 81+12x=24x+9 | | 35=10^x | | -17x−11=−62. | | 23+3x+6=90 | | 82=9/5c+32 | | -4(8x+2)=-5x-35 | | -17x-11=−62. | | 4b^2-10b+5=0 | | 15+3x+6=90 | | x4-3x+1=0 | | r4+ 8= 10 | | 15+8+3x+6=90 | | 4-1x=7x+100 | | 84=4+1.2x | | v+32=9 | | 20=x÷2-10 | | c-263=7+7 | | 2x-3x-7=4x-10 | | C=37.98+25x | | -3+6x=4x+7 | | -1x+7=2x+4 | | x^2+14^x+45=0 | | 5566=35(p+36) | | 3(x+2)+24+90=180 | | 10-2(x-1)-5x=x-40-x | | 5x+4=6x+59 | | 1500x=7.25 | | 3+x7=52 | | x-2x-x=-10-4x+6 | | 1500x=120 | | 2x+3x+5+90=180 | | 5u2+9u–6=0 |